Modernization and Inheritance of Folk Beliefs in the Digital Age: A Case Study in the Southeastern Coastal Areas of China - Liu, Guoliang (Religions, 2024)
With the processes of urbanization and population migration in China, local traditional folk beliefs are facing a crisis of inheritance, including the loss of believers and the decline of religious buildings. However, in the southeastern coastal areas of China, with the development of society and the advancement of science and technology, folk beliefs have shown a trend of modernization, gained widespread attention from young people, and shown a good trend of inheritance. This study focuses on the modernization of folk beliefs in the southeastern coastal areas of China, exploring how folk beliefs are adapted to contemporary life and the key role of information technology in the protection of religious buildings. The study found that the modernization of folk beliefs in China’s southeastern coastal areas is mainly reflected in the portrayal of gods in cartoonish images, the popularity of music, and the modernization of communication methods. By analyzing the modernization process of folk beliefs in the southeastern coastal areas of China, this study reveals the adaptation and development of folk beliefs in modern society. Based on the reality of contemporary Chinese society, this study also explores the future modernization trend of folk beliefs and discusses the possibilities and potential risks of the application of digital technology in folk belief inheritance.